2014
DOI: 10.7327/cerei.2014.06.03
|View full text |Cite
|
Sign up to set email alerts
|

Application of the analytic hierarchy process method in a comparison of financial leasing and loans

Abstract: Decision making is an integral part of all business processes. Some decisions are spontaneous and others time consuming, requiring detailed information about their implications. Decision making can be performed according to perspectives that may also be conflicting in nature. Models that are helpful in dealing with such problems are multi-criteria decision-making methods. The most important method in this group is the analytic hierarchy process. The principle of the analytic hierarchy process is the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Pukala and Petrova (2019) proposed a Analytic Hierarchy Process (AHP)-based approach to the process of financing innovation sources selection by companies. In the mining industry, Chalúpková & Franek (2014) introduced an AHP-based decision support system in a comparison of financial leasing and loans processes. The research employed AHP and sensitivity analyses to select the optimal form of asset acquisition based on clients' selected criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pukala and Petrova (2019) proposed a Analytic Hierarchy Process (AHP)-based approach to the process of financing innovation sources selection by companies. In the mining industry, Chalúpková & Franek (2014) introduced an AHP-based decision support system in a comparison of financial leasing and loans processes. The research employed AHP and sensitivity analyses to select the optimal form of asset acquisition based on clients' selected criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a research of selecting the best financial leasing case for bank customers, Chalúpková and Franek (2014) summarized that the best alternative for a customer is not being sensitive to a change in the weights estimated by the AHP in their research. For determining the weights of the RFM model, some relevant studies were applied in different industries, such as Shih and Liu (2003) applied the AHP procedure to determine the weights of the RFM model and sort the customer values.…”
Section: Analytic Hierarchy Process Proceduresmentioning
confidence: 99%
“…The identification and evaluation of the factors in FSCM adoption is not easy. Chalupakova et al [23] found that some decisions are spontaneous and others time consuming, requiring detailed information about their implycations. Author used AHP method because AHP can show a detailed version of problem in a structured way.…”
Section: Literature Reviewmentioning
confidence: 99%